Method for preparing of germinated brown rice (GBR) porridge. - Azlan, Azrina; Amom, Zulkhairi; Mohd Esa, Norhaizan; Abd. Kadir, Khairul Kamilah; Ismail, Maznah (2009)

(untitled)
This invention relates to a method for preparing of germinated brown rice porridge with enhanced cooking and nutritional properties. Its improved cooking properties is characterized by shorten cooking time, reduce brown color and less rancid odor. The method of preparation of germinated brown rice porridge comprises the step of heating, modifying the grind to non-grind ratio of germinated brown rice, soaking, steaming, and drying. Finally, adding spices and flavors and applying microwave treatment.